1977
DOI: 10.1115/1.3426290
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental and Theoretical Investigation of Hypothermia in Dogs

Abstract: A technique for post surgical rewarming from clinical hypothermia, which utilizes a thoracic flush with heated saline solution, has been investigated experimentally and theoretically. The rewarming technique was used in conjunction with surface cooling for eighteen separate experiments using mongrel dogs, with the thermal response of the animals determined from thermocouple measurements at twelve strategic locations. Utilizing these measurements, temperature histories were established for the animals, from whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…In the experiment, if the dog's temperature reached a critical temperature, the environ ment was changed, thus changing the response of the dog. Mauck et al (1977) provide a model of a dog during hypothermia.…”
Section: Core Of the Torsomentioning
confidence: 99%
See 4 more Smart Citations
“…In the experiment, if the dog's temperature reached a critical temperature, the environ ment was changed, thus changing the response of the dog. Mauck et al (1977) provide a model of a dog during hypothermia.…”
Section: Core Of the Torsomentioning
confidence: 99%
“…In the Mauck et al (1977) (Mauck et al, 1977) The results of their model are shown in Figure 7. A fairly good reproduction of the experimental results is obtained.…”
Section: Core Of the Torsomentioning
confidence: 99%
See 3 more Smart Citations